AAK aims to reduce climate impact of their produce through interventions at chain level (incl. valorization of residues thus loss reduction) by using a dedicated version of the ACE calculator - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
AAK aims to reduce climate impact of their produce through interventions at chain level (incl. valorization of residues thus loss reduction) by using a dedicated version of the ACE calculator. AAK states that scope 3 emissions reduction is considered promising. Next, they are curious about the relevancy of side stream valorization and how logistic choices affect GHG emission of their products.